Potential of urinary apolipoprotein A1 as a biomarker for coronary artery disease in young adults - Mohamed Bakrim, Norbaiyah; Abdullah, Aszrin; Wan Omar, Wan Fatein Nabeila; Hamidon, Nurul Nadiah; Muid, Suhaila; Badrulhisham, Aisyah (2023)
INTRODUCTION: Coronary artery disease (CAD) in young adults associate with significant socio-economic burden to individuals, families and community. Studies on new protein biomarkers to improve risk stratification of CAD in young adults mainly focused on plasma samples, while urinary biomarkers remain minimally researched. Hence, this study aimed to investigate the urinary concentration of Apolipoprotein A1 (ApoA1) in young patients with acute myocardial infarction (AMI). MATERIALS AND METHOD: This study recruited 40 newly diagnosed AMI patients and 40 healthy control subjects aged 18 to 45 years. Urine samples were collected from all subjects and centrifuged. Following removal of the sediment, the supernatant was collected and stored at -80 °C until analysis. The urinary concentration of ApoA1 were measured using the Abcam Human ApoA1 enzyme-linked immunosorbent assay kit. Risk factor profiles for CAD such as smoking status, body mass index, blood pressure, plasma total cholesterol and glucose levels of all subjects were determined and documented. RESULTS: The mean age of AMI patients and the controls was 37.1 ± 5.2, and 31.6 ± 8.1 years, p<0.05, respectively. The urinary concentration of ApoA1 was significantly higher in AMI patients than controls (12.442 ± 3.571 vs. 10.067 ± 5.606 ng/mL, p<0.05). After controlling for other CAD risk factor, there was no significant association between urinary ApoA1 and AMI status in young adults (Odd ratio = 3.123, 95% CI: 0.756-1.015, p>0.05). CONCLUSION: A significant elevation of urinary excretion of ApoA1 in AMI young adults proposed its potential role as a urinary biomarker for CAD in young adults. Urinary biomarker may serve as an alternative non-invasive approach to recognize early onset of CAD in this cohort.